The radical pair mechanism cannot explain telecommunication frequency effects on reactive oxygen species - Talbi, Owaiss; Zadeh-Haghighi, Hadi; Simon, Christoph (Frontiers in Quantum Science and Technology, 2025)
Electromagnetic radiation at telecommunication frequencies has been reported to have biological effects, particularly affecting the production of reactive oxygen species, raising the question of potential mechanisms. In this study, we explored whether the radical pair mechanism (RPM) could account for these effects. Given that telecommunication frequencies are much higher than those associated with typical hyperfine interactions in biological systems, any effects would necessarily be non-resonant. Our computational simulations confirm that the RPM cannot explain these effects under experimental conditions due to the negligible influence of low-amplitude oscillating fields. We find that observable effects on radical pairs at telecommunication frequencies would require hyperfine coupling constants that are precisely fine-tuned to values far exceeding those naturally occurring in biological systems. We conclude that another mechanism must be responsible for the effects of telecommunication frequency fields in biological systems.